The Influence of Student Learning Outcomes and Practical Facilities in Schools on Industrial Work Practice Results - Aryanto, Hendra; Ahyani, Nur; Tahrun, Tahrun (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the effect of student learning outcomes and practical infrastructure on the results of industrial work practices at UPT SMK Negeri 4 Muara Enim. This study uses a quantitative method with an ex post facto approach. The data obtained were analyzed using by SPSS (Statistical Product and Service Solution) version 25.0 for windows. This study shows that there is an effect of learning outcomes on the results of industrial work practices with a t-count of 4.450 and a t-table of 1.9855,. There is an influence of practical infrastructure in schools on the results of industrial work practices with a t-count of 11.888 and a t-table of 1, 9855. There is an effect of student learning outcomes and industrial work practice infrastructure together on the results of industrial work practices with an f-count of 64,284 and f-table of 3,0933. The conclusion of this study is that the results of industrial work practices can get good results if student learning outcomes are good and practical infrastructure is adequate.